SOME PROBLEMS IN THE IMPLEMENTATION OF GOVERNMENT PROCUREMENT AND SOLUTIONS - Karimjonova Munavvar Ibragimovna; Benjamin Franklin (Proximus Journal Publishing, 2024)
This article highlights the importance of public procurement in the effective and targeted use of budget funds, as well as the analysis of the ambiguities in some normative legal documents adopted in relation to its implementation, as well as the analysis of cases of violations of the law in the implementation of public procurement, as well as scientific proposals and recommendations for its prevention.
Keywords: public procurement; regulatory legal documents